Electronic banking for SMEs: a case study of Fortis Bank UK. (9th November 2004) - Brown, Ann; Remenyi, Dan; Bajomo, Adeolu
This paper focuses on the UK banking industry's current approach to meeting the banking needs of SMEs. It investigates the questions raised by the industry's assumptions that internet banking will replace PC based banking as the preferred electronic channel between banks and their SME clients in the future. The case reports on the 2-year project at Fortis UK to develop and sell an internet business banking service to its SME clients. SME response has been unexpectedly negative. The paper explores the reasons for this and proposes a model of the factors that affect adoption, for SMEs.